2009
DOI: 10.1093/cs/31.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Best Practice Program for Low-Income African American Students Transitioning from Middle to High School

Abstract: On the basis of systematic evaluation of three program databases, totaling 246 programs, this article provides a discussion on a best practice program for low-income African American students transitioning from middle school to high school in urban school settings. The main research question was "Of the programs touted as best practice, is there one that could produce positive middle school transition outcomes for low-income African American students in urban school settings?" To allow for the examination of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This result is consistent with findings of increased academic achievement following multidisciplinary truancy interventions (Smyth, ; Wilkins, ). Gentle‐Genitty () indicated that tutoring may increase a student's connection to school and thus decrease the likelihood of missing or leaving school. Many youth in the TDP reported that academic assistance and/or tutoring was the most helpful component of the program.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with findings of increased academic achievement following multidisciplinary truancy interventions (Smyth, ; Wilkins, ). Gentle‐Genitty () indicated that tutoring may increase a student's connection to school and thus decrease the likelihood of missing or leaving school. Many youth in the TDP reported that academic assistance and/or tutoring was the most helpful component of the program.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Dupéré et al (2018) found that approximately 40% of students who dropped out did so when they were recently exposed to at least one event considered moderately or severely stressful. The transition to high school could be considered a stressful event, as it is a key point when academic, contextual, social, and personal trajectories meet and make it difficult for students to overcome its trials and emotional strain Gentle-Genitty, 2009). Youngman (1986) stated that in 1986, 10% of British students suffer serious problems after they enter high school.…”
Section: The Dropout Crisismentioning
confidence: 99%
“…Structure and context. Upon arriving to high school students must navigate a larger school with a new layout and a greater, more diverse population (Felmee et al, 2018, Gentle-Genitty, 2009. In addition, they must adapt to new schedules, class expectations and procedures through developing skills like organization and time management .…”
Section: Institutional Factorsmentioning
confidence: 99%
See 2 more Smart Citations